Administrative service quality in higher education: does it impact faculty satisfaction, engagement, and performance? (Revista Electrónica Calidad en la Educación Superior, 2025)
This study examines the effects of administrative service quality on satisfaction, engagement, and performance among university faculty at a higher education institution in Costa Rica. Using a mixed-methods approach that included questionnaires and a focus group, it was found that service quality influences faculty satisfaction and performance, but not their level of engagement. The results indicate that satisfaction is mainly affected by limited support in administrative tasks. As for commitment, it impacts faculty performance and is influenced by factors such as pride, motivation, and recognition for working at the institution.
Keywords: quality; administrative service; satisfaction; engagement; performance; higher education